2021
DOI: 10.21873/anticanres.15110
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-based Cancer Immunotherapy: Challenges and Opportunities for IL-10

Abstract: Cancer immunotherapy is an evolving field of research. Cytokines have been conceptualized as an anticancer therapy for longer than most other cancer immunotherapy modalities. Yet, to date, only two cytokines are FDA-approved: IFN-α and IL-2. Despite the initial breakthrough, both agents have been superseded by other, more efficacious agents such as immune checkpoint inhibitors. Several issues persist with cytokine-based cancer therapies; these are broadly categorised into a) high toxicity and b) low efficacy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…IL-10 plays a pleomorphic role in cancer immunity [93]. It has been classically considered an immunosuppressive factor that promotes tumor growth, while recent studies showed exogenous IL-10 administration can induce anti-tumor effects by promoting CD8 T cell-mediated anti-tumor immunity [94,95].…”
Section: Il-10mentioning
confidence: 99%
“…IL-10 plays a pleomorphic role in cancer immunity [93]. It has been classically considered an immunosuppressive factor that promotes tumor growth, while recent studies showed exogenous IL-10 administration can induce anti-tumor effects by promoting CD8 T cell-mediated anti-tumor immunity [94,95].…”
Section: Il-10mentioning
confidence: 99%
“…IL-10 induced Fas/FasL pathway is important for disease control and has otherwise been an under reported functional mechanism of IL-10 signaling ( Figure 1 ) ( 50 – 52 ). Similarly, IL-10 has also been shown to induce the production of cytotoxic enzymes and IFNγ in CD8 + T-cells, and, in conjunction with IL-2, differentiation of cytotoxic T-cells from their precursors, demonstrating a dual function of IL-10 signaling in immune regulation ( 53 , 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 44/70 immunomodulators in the TCGA-LUAD cohort and 57/70 immunomodulators in the TCGA-LUSC cohort presented significant correlation with the transcript level of IFI44L . As reported, the immunomodulators have tremendous and abundant functions in the TME, as well as tumor development and progression ( 35 , 36 ). Among these immunomodulators, there are considerable proportions of tumor necrosis factor (TNF) and its receptor (TNFR); as the term suggest, they belong to the tumor necrosis factor super family (TNFSF) and tumor necrosis factor receptor super family (TNFRSF).…”
Section: Discussionmentioning
confidence: 95%